Analisis Kompetensi Dan Kesesuaian Jabatan Menggunakan Asesmen Psikologis: Studi Kasus Seleksi Karyawan Bidang Sales Agroindustri - Roys Dwi Nugroho; Yanto Prasetyo (Universitas Muhammadiyah Gresik, 2026)
Background: The agro-industry sector requires a selection process that ensures alignment between candidates’ psychological characteristics and the complex demands of the job, particularly for the position of Regional Sales Coordinator (KPD), which requires strong analytical ability, interpersonal competence, work endurance, and achievement motivation. Objective: This study aims to describe the implementation of psychological assessment in selecting candidates for the KPD position, evaluate the relevance of assessment results to the required job competencies, and identify the implications of these results for employee placement decisions. Method: Using a qualitative case study approach, data were collected through psychological tests (IST, Kraeplin, Papikostik, 16PF, and projective tests), behavioral event interviews, interviews with HR and user representatives, and direct observation. Thematic analysis and triangulation were conducted to ensure the consistency and validity of interpretations. Result: The findings indicate that the candidate demonstrates good analytical ability and emotional stability but shows weaknesses in numerical ability, work pace, achievement motivation, interpersonal skills, and independent decision-making—core competencies required for the KPD role. Conclusion: The results suggest a mismatch between the candidate’s psychological profile and the demands of the position. The study concludes that multi-method psychological assessment provides a more accurate understanding of person–job fit and plays an essential role in selection decisions and competency development recommendations within the agro-industry sector.